Motor transport safety in traffic safety sistems - Stepanov, O.; Степанов, А. В. (Харківський національний автомобільно-дорожній університет, 2015)
This article considers various approaches to motor transport safety in traffic safety system. Much attention is paid to a complex method of increasing the efficiency of a system for keeping active safety. On the basis of authors research it is suggested to solve the problems of motor transport safety in traffic safety system through certain methodology of approach to the analysis and solution to the problem of motor transport safety management in a safety system of the Driver - Automobile - Road - Environment (DARE) complex.
Безопасность автотранспорта в системе безопасности дорожного движения
Безпека автотранспорту в системі безпеки дорожнього руху
Keywords: motor transport safety; traffic safety; active safety; безопасности автотранспорта; безопасность дорожного движения; активная безопасность; безпеки автотранспорту; безпеку дорожнього руху; активна безпека; 656.13